2018
DOI: 10.1021/acs.nanolett.8b01916
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Morphology in Polycrystalline Films by Nucleation and Growth from Metastable Nanocrystals

Abstract: Solution processing of polycrystalline compound semiconductor thin film using nanocrystals as a precursor is considered one of the most promising and economically viable routes for future large-area manufacturing. However, in polycrystalline compound semiconductor films such as CuZnSnS (CZTS), grain size, and the respective grain boundaries play a key role in dictating the optoelectronic properties. Various strategies have been employed previously in tailoring the grain size and boundaries (such as ligand exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Moreover, the negative Gibbs (Δ G < 0) energy released from the oxidation reaction drives the replacement reaction between CuO and Zn, which shows the presence of a ZnO layer on the surface (eq 1, Supporting Information). Thus, we speculate that the released negative Gibbs energy drives the surface diffusion during the thermal treatment in air, which is achieved from the oxidation reaction and following replacement reaction. , A mass loading of about 1.02 mg cm –2 (the calculation and discussion in the experimental section of the Supporting Information) and thickness of about several micrometers ZnO layer on the surface of the brass mesh was successfully prepared using a simple thermal treatment. Furthermore, series of oxidation experiments at various temperatures were conducted to study the morphology evolution process and composition on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the negative Gibbs (Δ G < 0) energy released from the oxidation reaction drives the replacement reaction between CuO and Zn, which shows the presence of a ZnO layer on the surface (eq 1, Supporting Information). Thus, we speculate that the released negative Gibbs energy drives the surface diffusion during the thermal treatment in air, which is achieved from the oxidation reaction and following replacement reaction. , A mass loading of about 1.02 mg cm –2 (the calculation and discussion in the experimental section of the Supporting Information) and thickness of about several micrometers ZnO layer on the surface of the brass mesh was successfully prepared using a simple thermal treatment. Furthermore, series of oxidation experiments at various temperatures were conducted to study the morphology evolution process and composition on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there are also some unique methods to fabricate the lithiophilic coatings over hosts. Heating brass mesh (Zn–Cu alloy) at 300 °C in air produces a compact and even ZnO layer on the surface, which is ascribed to the atom diffusion on the surface driven by the Gibbs free energy decrement of the oxidation reaction (Figure c). ,, By applying the anode, the lithiophilic property gets improved a lot and the cells are able to stably run for 500 cycles at the current density of 2 mA cm –2 .…”
Section: Polymorphs Evolution Management Strategies Via Regulated Mul...mentioning
confidence: 99%
“…It was previously observed that wurtzite-to-kesterite phase transition at elevated temperature led to enhanced grain growth in w-CZTS nanorods. ,, Here, we demonstrate the generality of this phenomenon for various nanomaterials synthesized as metastable polymorphs by colloidal methods. Figure a shows the change of P-XRD patterns of zb-CdSe NCs with (N 2 H 5 ) 2 In 2 Se 4 ligands upon heating.…”
Section: Resultsmentioning
confidence: 99%
“…Sintering of micron and submicron powders is routinely used to improve mechanical properties, to increase electrical and thermal conductivity in ceramics, in powder metallurgy, for fabricating thermoelectric materials, and so on. On the other hand, preventing sintering of catalytically active metal clusters is an active area of research in heterogeneous catalysis. Colloidally synthesized NCs bridge the size gap between micron-sized ceramic powders and metal clusters, which are typically smaller than 2 nm. Sintering and grain growth of ALD-passivated PbS NCs, superlattices of PbSe NCs, CIGS NCs, and CZTS nanorods have been studied; ,, however, a systematic understanding of NC sintering and grain growth is largely lacking. Sintering studies of as-synthesized colloidal NCs are complicated by organic surface ligands that separate inorganic NC cores at room temperature but desorb and decompose upon heating .…”
Section: Introductionmentioning
confidence: 99%